1998
DOI: 10.1177/0734371x9801800403
|View full text |Cite
|
Sign up to set email alerts
|

Generational Comparisons of Public Employee Motivation

Abstract: This cross-sectional study reports the similarities and differences between three age cohorts of public employees—Generation X, Baby Boomers and Matures—on 15 motivational factors. While substantial differences are broadly observed between the generations outside the public sector organizational context, these age-based categories of public employees are nearly identical in the governmental workplace. The few differences found can be ascribed to life and career stages as opposed to cohort-specific sociological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
124
1
7

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(135 citation statements)
references
References 58 publications
3
124
1
7
Order By: Relevance
“…However, for the purpose of this study, boomers are people aged between 40 to 60 years old, while X-ers comprises those between 25 to 39 years of age (Kotler & Keller, 2006). The former embraces the idea of entitlement and expecting the best from life (Kupperschmidt, 2000), while the latter survives through rapid changes and insecurity, and lack of strong mores leading them into becoming more individualistic (Jurkiewicz & Brown, 1998). The results of the study of Smola & Sutton (2002) revealed that generational work values do vary and it does change as one ages, and saw that there has been an increased need for balance work and personal goals within the American labour arm.…”
Section: Research Questionmentioning
confidence: 82%
“…However, for the purpose of this study, boomers are people aged between 40 to 60 years old, while X-ers comprises those between 25 to 39 years of age (Kotler & Keller, 2006). The former embraces the idea of entitlement and expecting the best from life (Kupperschmidt, 2000), while the latter survives through rapid changes and insecurity, and lack of strong mores leading them into becoming more individualistic (Jurkiewicz & Brown, 1998). The results of the study of Smola & Sutton (2002) revealed that generational work values do vary and it does change as one ages, and saw that there has been an increased need for balance work and personal goals within the American labour arm.…”
Section: Research Questionmentioning
confidence: 82%
“…This generation tends to solve their problems on their own (Tulgan, 2000). Jurkiewicz and Brown (1998) and Yu and Miller (2005), wanted to take attention to the individualistic features of the Xers since they tend to look for any opportunities to improve their working skills and loyalty to their profession rather than to their employer.…”
Section: X Generationmentioning
confidence: 99%
“…Baby Boomers, Generation X, Y and Z, delineated by their birth years ( 1946-19651965-19801980-1995-Stredwick (2013) 1946-19641965-19791980-19901990s -2000s Knoll Inc (2014) -1965-19781979-19971998 Gilbert ( For the purpose of this research, the age bracket for Generation Z is assumed as those born 1995 and onwards.…”
Section: Social Generationsmentioning
confidence: 99%